Age and growth of the bull shark (Carcharhinus leucas) around Reunion Island, South West Indian Ocean. Issue 3 (17th June 2021) - Hoarau, Florian; Darnaude, Audrey; Poirout, Thomas; Jannel, Lou‐Anne; Labonne, Maylis; Jaquemet, Sébastien
Abstract: Sharks exhibit varied demographic strategies depending on both the species and the population location, which make them more or less vulnerable to fishing. Accurate evaluation of local age and growth parameters is therefore fundamental for the sustainable management of their stocks. Although demographic parameters have been assessed for bull shark ( Carcharhinus leucas ) populations in several locations of the world, this information is missing so far around Reunion Island, in the south‐west Indian Ocean. To fill this gap of knowledge, age and growth data were gathered from the vertebrae of 140 individuals of C. leucas (77 females and 63 males, mostly adults) fished around the island between 2012 and 2019. After verification of the annual deposition of growth band pairs on these structures using relative marginal increment analysis on 40 individuals, band pairs were counted along the vertebral centrum for each individual. Thanks to this approach, growth was shown to significantly differ between male and female C. leucas around Reunion Island, with respective von Bertalanffy growth model equations of L t = 314 1 − e − 0.0814 t + 5.45 and L t = 321.5 1 − e − 0.0999 t + 3.420 . Indeed, the females of the species fished in this area were significantly ( P < 0.001) larger than local males, with an estimated difference in size of 16.1 cm at 20 years old. They also apparently reach older ages, with an estimated maximum age of 33.50 years, against 29.75 years only for the males. The estimated size at birth around the island is larger than elsewhere in the world, varying from 92.30 to 100.00 cm depending on the method used. These results confirm that the population of C. leucas around Reunion Island exhibits a K‐selected strategy, which makes it highly vulnerable to fishing pressure.